87Sr/86Sr ratios discrimination applied to the main Paleozoic carbonate sedimentation in Ossa-Morena Zone - Moreira, Noel (2017)
The carbonated sedimentation in Ossa-Morena Zone during the Palaeozoic is formed, at least, by two main episodes. However, some chronological questions remain open, due to lack of biostratigraphic data in some carbonates. Sr isotope analysis was performed in selected limestones and marbles of Ossa-Morena Zone, in order to discriminate the Sr signature of the two main carbonate sedimentation episodes. The Sr isotopic data from the analyzed carbonate show two clusters of 87Sr/86Sr ratios, one related with the Lower Cambrian and other with the Lower-Middle Devonian carbonates.